Strategic Management Practices and Their Economic Impact ‎on SME Profitability in Emerging Markets - Mehta, Dr. Kirti; K A , Dr. Dhanya; Pandey , Dr. Ruchi; Sahu , Er. Sudhir Kumar; Vishwakarma , Dr. Vinayak; Gupta , Dr. Sayak (International Journal of Accounting and Economics Studies, 2026)
Small and Medium-sized Enterprises (SMEs) are crucial to economic growth and job creation, ‎especially in the complex and often volatile environments of emerging markets. Limited ‎strategic capacity and inconsistent performance hinder their potential. The study investigates the ‎impact of strategic management practices, specifically strategic planning, market orientation, ‎innovation, and financial control, on SME profitability across emerging economies in Asia, ‎Africa, and Latin America. A mixed-methods approach was used, combining quantitative ‎survey data from 310 SMEs with qualitative interviews of strategic decision-makers. Statistical ‎analyses, including correlation and multiple regression models, were employed to examine ‎relationships between strategic variables and financial indicators such as return on investment ‎‎(ROI), revenue growth, and net profit margin. The results showed that strategic planning had ‎the strongest positive correlation with ROI, followed by market orientation, while innovation ‎and financial control had minimal direct influence. Sectoral and regional differences were also ‎observed, with manufacturing SMEs showing stronger planning capabilities and Asian firms ‎outperforming others across all profitability measures. The qualitative data highlighted ‎contextual barriers and enablers shaping strategic decision-making. The findings emphasize the ‎importance of institutionalizing strategic planning and adopting market-responsive strategies to ‎enhance performance. Policymakers and development agencies should support capacity-‎building efforts and ensure necessary infrastructure is in place. Future research should explore ‎longitudinal and comparative approaches to deepen understanding of strategic dynamics in ‎various emerging market contexts‎.